Additive Manufacturing of Coplanar Transmission Lines on Alumina Substrate up to 24 GHz using Laser Assisted Selective Metallization - Lomakin, Konstantin; Wang, Li; Job, Alexander; Süß-Wolf, Robert; Franke, Jörg; Helmreich, Klaus; Gold, Gerald (2020 50th European Microwave Conference (EuMC), 2021)
This work proposes a novel approach for fabrication of high precision radio frequency circuits on low loss ceramic substrates by an additive manufacturing laser assisted selective metalization process. Coplanar waveguides are realized and measured with a GSG probe setup revealing an attenuation coefficient of approximately 110dB/m at 24 GHz, hence suggesting feasibility of the proposed approach. The simplicity of the process makes it an auspicious candidate for development of future communication and sensor applications due to the combination of high performance substrates and simple fabrication technique, while the required precision for mmWave range and above may be achieved by improving the optical laser system and metal platin

Application and development of analytic accelerated test models for the lifetime prediction of a novel contacting method - Friedlein, Matthias; Spahr, Michael; Süß-Wolf, Robert; Franke, Jörg (7. WGP-Jahreskongress, 2017)

Concept for Automated Fuse and Relay Assembly in the Field of Cable Harness Manufacturing - Heisler, Paul; Sand, Christian; Hefner, Florian; Süß-Wolf, Robert; Franke, Jörg (RWTH Aachen 2017 – 7. WGP-Jahreskongress, 2017)

Development and Validation of a Material Application Tool for the Covering Process of a Wire Harness - Heisler, Paul; Hausecker, Erik; Regler, Johannes; Süß-Wolf, Robert; Franke, Jörg (2020 10th International Electric Drives Production Conference, EDPC 2020 - Proceedings, 2020)
The wiring harness production in the automotive sector is still characterized by a high proportion of manual work. In particular, the process of taping the wire harness on the assembly boards with conventional adhesive tape is a very time-consuming manual work step. In order to automate this, various methods have already been tested and one of the most promising is the dosing process. Thereby a nozzle moves along the routed cables and covers them with silicone rubber. In order to apply this process successfully in practice, it is particularly necessary to sheat variable wire harness geometries that differ in terms of their diameter and composition. In scope of this work, a nozzle was developed, which can be infinitely adjusted to different cable strands using an iris diaphragm mechanism. The fused deposition modelling (FDM) process was used for fast production and testing of various nozzle construction. In addition to various cable harnesses, concepts were developed and validated in order to cover nodes or branch points with the dosing process. All experiments were carried out in the form of model tests in terms of their applicability in practice.
CRIS-Team Scopus Importer:2023-03-07
Keywords: automation; automotive industry; dosing process; silicone rubber; taping; wiring harness; wiring harness production

Failure dependent progression of contact resistance in thermal-shock testing of spring-clip contacts - Friedlein, Matthias; Spahr, Michael; Süß-Wolf, Robert; Franke, Jörg (2017 IEEE Holm Conference 2017, 2017)
Through ever changing terms and regulations on fuel consumption and emissions, weight becomes the number one concern of car manufacturers. Meeting those new regulations and the customer's desire for more options and variations is only possible without adding more weight by changing the wiring harnesses' technology. One solution to face this problem can be found by the application of flexible flat cables (FFCs) instead of common round cable wire systems. For a holistic approach, it is important not only to establish automated ways of cable installation, but also methods of automatically contacting components. Therefore, a new direct contacting method was developed at the Institute for Factory Automation and Production Systems (FAPS). The innovative contacting method enables to contact an automatically mounted one side accessible FFC with kinematic systems of industrial robots in an automated way. However, before new technologies can be applied to serial production, car manufacturers demand standardized climatic tests. In this paper, a correlation was discovered between the progression of contact resistance and failure mechanisms during thermal shock testing. Furthermore, an influence of different peak temperatures and materials was identified and the results were verified via SEM micrographs.
Keywords: thermal-shock testing; automotive wire harness; reliability; contact resistance; degradation mechanisms

Innovative signal and power connection solutions for alternative powertrain concepts - Fröhlig, Simon; Piechulek, Niklas; Friedlein, Matthias; Süß-Wolf, Robert; Schmidt, Lorenz; Kuhn, Marlene; Wang, Li; Hefner, Florian; Heisler, Paul; Fröhlich, Jan; Meiners, Moritz; Franke, Jörg (2020 10th International Electric Drives Production Conference (EDPC), 2020)
Since the automotive wiring harness interconnects all electrical components in a vehicle, it also must adapt to all componential, mechanical, and electrical architecture changes. For this reason, almost all trends that affect the vehicle in general also affect the wiring system. This paper describes the current situation, analyses the most important trends in the automotive industry, and discusses their effects on the wiring system. In particular, the focus is on the current megatrend of electromobility and the associated electrification of the powertrain. In addition to the integration of autonomous driving functions and Car-To-X- Communication, the electrification adds new requirements and tasks for the wire harness. In this context, a holistic approach is taken to combine various fields of research such as automation solutions, computer-aided technologies, functional integration, as well as reliability models to offer a solution for the challenges caused by current automotive trends.<br
Keywords: electromobility; wiring harness; vehicle electrical system; signal and power connection; alternative powertrain

Innovative Solutions for the Covering Process in the Manufacturing of Wire Harnesses to Increase the Automation Degree - Heisler, Paul; Kuhn, Marlene; Süß-Wolf, Robert; Franke, Jörg (2020 IEEE 11th International Conference on Mechanical and Intelligent Manufacturing Technologies (ICMIMT), 2020)

Investigation of the laser ablation threshold for optimizing Laser Direct Structuring in the 3D-MID technology - Wang, Li; Süß-Wolf, Robert; Ulm, Michael; Franke, Jörg (ICEP-IAAC 2018 Proceedings, 2018)
Keywords: 3D-MID; LDS; Laser ablation threshold; Laser activation; Laser roughening

Laser-Associated Selective Metallization of Ceramic Surface With Infrared Nanosecond Laser Technology - Wang, Li; Fu, Zongwen; Süß-Wolf, Robert; Travitzky, Nahum; Greil, Peter; Franke, Jörg (Advanced Engineering Materials, 2019)

Novel Ceramic-Based Material for the Applications of Molded Interconnect Devices (3D-MID) Based on Laser Direct Structuring - Bachy, Bassim; Süß-Wolf, Robert; Wang, Li; Fu, Zongwen; Travitzky, Nahum; Greil, Peter; Franke, Jörg (Advanced Engineering Materials, 2018)
Molded interconnect devices (MID) based on laser direct structuring LPKF-LDS® technology are widely used in the realm of electronics. Nowaday, design and development of new materials with improved properties for 3D-MID are in focus. In this work, novel materials based on alumina ceramic with copper oxide additives are developed for this technology. The effect of the sintering temperature and the doping amount of copper oxide on the metallization quality is investigated. Furthermore, the influence of laser process parameters (e.g., laser power, velocity’, and frequency) on process output namely groove dimensions, groove profile, characteristics of structured area, and quality of the final 3D-MID products are discussed. The novel ceramic materials show high flexibility to realize very fine structures. Moreover, the laser-structured and metallized area shows a free edge lap with good quality. After metallization high accuracy with copper line/pitch of 16 μm/20 μm is achieved.
CRIS-Team Scopus Importer:2023-03-07
Keywords: High-Performance Ceramics; Laser Direct Structuring; Molded Interconnect Devices

On the quality and the accuracy of the laser direct structuring, experimental investigation and optimization - Bachy, Bassim; Süß-Wolf, Robert; Franke, Jörg (Journal of Laser Applications, 2018)
The enormous applications of the molded interconnect devices (MID) make these face many difficult challenges, some of which are the quality and the reliability, as well as concerns on how to produce the micro-MID products. This drives to a hard competition between the different methods used in the MID technology. The laser direct structuring (LDS) has clearly been distinguished as the best method in comparison with the other MID processes. However, it also needs more development, especially in terms of the quality, accuracy, and their impact on the final MID quality of the two- (2D) and three-dimensional (3D) micro and normal products, especially with the decline or the limited availability of information in both of the industry and scientific research. In this work, the MID-LDS has been experimentally investigated by considering the effect of the important process parameters on the process responses and then to explore the relationship between these responses and the final MID quality and reliability. These experimental works were based on the design of the experimental tool, which employed a full factorial design for the LDS process parameters. They include the laser power, structuring speed, laser frequency, hatching percentage, the incident angle, and the focal length. The experiments have been performed on the polymer plates of Poly Ether Ether Ketone (PEEK) materials. During the experiments, different measurements have been implemented to find out the correlation between the adopted parameters and the 3D surface roughness, structuring percentage, structuring type, and ablation type, which are regarded as the most important features of LDS quality. Further measurements focus on the LDS accuracy and the final quality and reliability of the metallization structure, which includes the metallization thickness, the surface roughness, and the adhesion strength. The analysis of these experimental results showed that the quality and reliability, especially the adhesion strength and the surface roughness, of the final MID products are deeply related to the structuring percentage, structuring type, ablation type, and finally, the surface roughness.
CRIS-Team Scopus Importer:2023-03-07
Keywords: laser direct structuring; LDS accuracy; LDS quality; MID reliability; molded interconnect devices

Prediction of surface roughness of laser selective metallization of ceramics by multiple linear regression and artificial neural networks approaches - Wang, Li; Silva, Lisbeth; Süß-Wolf, Robert; Franke, Jörg (Journal of Laser Applications, 2020)
Laser selective metallization of ceramics (LMC) has been widely applied to prepare high-quality electrical patterns on ceramic circuit carriers. As the dominating factor, surface roughness after laser treatment is controlled mostly by the laser technical parameters, such as laser power, scanning velocity, and laser frequency. Therefore, establishing an accurate relation between the surface roughness and the laser parameters will be of great benefit to the LMC specimens. In the present research, machine learning is used to simulate the LMC process on an alumina-copper oxide ceramic. The effect of each laser parameter and the interaction between them are revealed by the multiple linear regression method. The artificial neural network model trained with the Levenberg-Marquardt function provides the best estimation of the surface roughness after laser treatment compared with the Bayesian-regularization function and the scaled-conjugate-gradient function. The result can be used as a practical prediction and reasonable guideline for the optimization of LMC processes.
CRIS-Team WoS Importer:2020-11-27

Robot-based automated production of wrapped connections with single solid round wires - Hefner, Florian; Herbert, Meike; Sjarov, Martin; Süß-Wolf, Robert; Franke, Jörg (Production at the leading edge of technology, 2019)
The solderless wrapping process is an electrical connection technology. It is mainly used in applications which require high reliability, such as the aerospace industry. A single solid conductor is wrapped around a connecting terminal. The process is currently being realized manually and the worker's qualification highly determines the overall process quality and efficiency. The challenges of this specific task include the handling of the flexible wire, the production process of standard-conforming wrapped connections and the required positioning accuracy of the tool relative to the wrappost. An automation of the production process is essential to meet the increasing quality and efficiency requirements of modern production environments, however, available solutions still highly rely on the operator and therefore lack the aspired automation degree. To enable the automated production of wrapped connections, a lightweight robot is equipped with several components. In this paper, the design of the whole system, including the newly developed robotic end-effector, is presented. The main components are two wrapping tools, each driven by an electric motor and attached to an electric slide. The device can be moved onto the wrappost extending the electric slide. A wire feeder realizes the conveying movement of the wire. Moreover, an optical sensor is used to determine the wrappost's position and orientation. The newly developed system enables the automated production of wrapped connections conforming to standards.<br
Keywords: wrapped connections; robot-based automation; flexible manufacturing

Simulation and experimental investigation for the 2D and 3D laser direct structuring process - Bachy, Bassim; Süß-Wolf, Robert; Kordaß, Timo; Franke, Jörg (International Journal of Advanced Manufacturing Technology, 2017)
The molded interconnected devices (MID) technology is vastly growing as an important innovative technology in the field of electronics production. The laser direct structuring (LDS) method is one of the most common available technologies for building up MID’s products. The current existing knowledge in industry and in research about the standards in the respective manufacturing processes and process parameters is up to now not fully comprehensive in terms of mutual influencing and dependencies on each other. This is particularly the case for the three-dimensional applications and micro products. In the present contribution, a new simulation procedures based on a three-dimensional finite element model (FEM) has been developed. The effect of each of latent heat of fusion and temperature on the material properties as well as the 3D Gaussian heat source for the laser beam has been considered in this work. The used material was a polymer plate poly ether ether ketone (PEEK). The effect of the process parameters including laser power, speed, frequency, hatching percent or overlap between the laser lines, the laser incident angle, and the focal length have been investigated in experiments and simulations. The present simulation can be used to predict, temperature distribution, maximum temperature, groove dimensions, and groove profile at different process parameters setup. The theoretical and the experimental results can show a good accordance. It can be concluded that the FEM simulation can be used efficiently for predicating, analyzing, and optimizing the 2D/3D laser parameters for the LDS process.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Finite element model; Laser direct structuring process; Laser process simulation; Molded interconnect devices

Simulation Assisted Characterization of Attenuation at Microstrip Transmission Lines fabricated by Laser Direct Structuring - Wang, Li; Lomakin, Konstantin; Job, Alexander; Süß-Wolf, Robert; Gold, Gerald; Franke, Jörg (2021 14th International Congress: Molded Interconnect Devices, MID 2021 - Proceedings, 2021)
This paper aims to provide a design approach to predict the attenuation of microstrip transmission lines fabricated by Laser Direct Structuring (LDS) on LDS polymer substrates. The impact of conductor and dielectric losses are separately considered in full wave simulation to evaluate the order of corresponding contribution to the total attenuation. Impact of surface roughness on signal propagation is taken into account by the Gradient Model. Simulations are compared with measurements of fabricated microstrip lines. The result also gives an estimation on the applicability of the LDS process towards radio frequency components.
CRIS-Team Scopus Importer:2021-04-02
Keywords: component; formatting; insert (key words); style; styling